The impact of Spanish on English vocabulary since 1901: an overview of the various subject fields influenced by Spanish in recent decades - Landmann, Julia (English today, 2018)
While there are numerous investigations of the impact of English on Spanish vocabulary, the opposite direction of lexical borrowing has as yet received fairly little attention. Spanish-derived words and meanings which have been taken over into English in the last few decades have been relatively neglected. The present article gives essential insight into the influence of Spanish on the English lexicon since 1901. I assign the different twentieth and twenty-first century Spanish borrowings to various lexical domains in order to offer an overview of the subject areas and fields of life to which Spanish has added new words and senses in recent times.
Published online by Cambridge University Press: 11 October 2017
Gesehen am 27.08.2019